Current Trends and Practices in Human Resource Management: A Case Study in YTL Power Services Sdn. Bhd. - Krishnan, Santhana (1998)
The challenging and changing role of human resource practitioners from merely administrative functions to strategic business partner calls for a more systematic and scientific approach as to how human resource should be practised. These practices have direct bearing on the performance of the human resources in an organization. Human resources play a vital role in the success of an organization. As such, there is a need to carry out studies on these practices which would enhance the potentials of the human resources in an organization. For the purpose of this study, YTL Power Services, an Independent Power Producer in our country has been selected. The current trends and practises in human resources management have been sought from contemporary literatures. These include articles from magazines such as HR Magazine from the United States. The review of related literatures provided the knowledge of the current trends and practices in human resources management. In this study, the findings from the review of related literature is called "what ought to be". On the other hand, the analysis on what is currently practised in YTL Power services is called "what is". The main objective of this study was to compare the existing human resource management practises in YTL Power Services and the current trends and practises recommended by the literatures. This study also intends to set a foundation for further research and study to more Malaysian companies on the human resource practises to further improve their human asset through current trend and practises in human resource management. The findings of this study are discussed by dividing it to seven sub - topics namely : • Reward and recognition • Career development and succession planning • Performance management • Recruitment and selection • Training and development • Communication and employees involvement • Corporate culture Finally, from the findings and review of related literature, this study makes some recommendations with the intention of closing or at least narrowing the gap between "what is" and "what ought to be".